Bending the Future : Fifty Ideas for the Next Fifty Years of Historic Preservation in the United States - Page, Max; Miller, Marla R. (Book collections on Project MUSE., 2016)
"The year 2016 marks the fiftieth anniversary of the National Historic Preservation Act, the cornerstone of historic preservation policy and practice in the United States. The act established the National Register of Historic Places, a national system of state preservation offices and local commissions, set up federal partnerships between states and tribes, and led to the formation of the standards for preservation and rehabilitation of historic structures. This book marks its fiftieth anniversary by collecting fifty new and provocative essays that chart the future of preservation. The commentators include leading preservation professionals, historians, writers, activists, journalists, architects, and urbanists. The essays offer a distinct vision for the future and address related questions, including: Who is a preservationist? What should be preserved? Why? How? What stories do we tell in preservation? How does preservation contribute to the financial, environmental, social, and cultural well-being of communities? And if the 'arc of the moral universe ... bends towards justice, ' how can preservation be a tool for achieving a more just society and world?"--Provided by publisher.